The homecoming [videorecording (DVD)] : a Christmas story - Cook, Fielder, 1923-2003; Neal, Patricia, 1926-2010; Thomas, Richard, 1951-; Bergen, Edgar, 1903-1978; Corby, Ellen; Hamner, Earl, Jr (Paramount DVD collection, 2003)
Set on a Depression Christmas Eve in 1933, this heart-tugging story centers around the Waltons, a rural family, as they prepare to celebrate Christmas together.